2010
DOI: 10.1103/physreva.82.043817
|View full text |Cite
|
Sign up to set email alerts
|

Coherent dual-comb spectroscopy at high signal-to-noise ratio

Abstract: Two coherent frequency combs are used to measure the full complex response of a sample in a configuration analogous to a dispersive Fourier transform spectrometer, infrared time domain spectrometer, or a multiheterodyne laser spectrometer. This dual comb spectrometer retains the frequency accuracy and resolution of the reference underlying the stabilized combs. We discuss the specific design of our coherent dual-comb spectrometer and demonstrate the potential of this technique by measuring the overtone vibrati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
179
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(180 citation statements)
references
References 67 publications
1
179
0
Order By: Relevance
“…The combs span 50 cm À 1 with a comb line spacing of 0.25 cm À 1 , resulting in 200 lines for each comb. In contrast to conventional frequency combs based on mode-locked lasers, the optical spectrum of FM combs does not show a gaussian envelope 7 , rather a complex amplitude distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combs span 50 cm À 1 with a comb line spacing of 0.25 cm À 1 , resulting in 200 lines for each comb. In contrast to conventional frequency combs based on mode-locked lasers, the optical spectrum of FM combs does not show a gaussian envelope 7 , rather a complex amplitude distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, several spectroscopy techniques using frequency combs have been demonstrated in various parts of the optical spectrum 2 . In the context of molecular spectroscopy, dual-comb spectroscopy [3][4][5][6][7][8][9] was proposed as an intriguing form of Fourier transform spectroscopy technique, showing a dramatic reduction in measurement times. The mid-infrared part of the optical spectrum is of paramount importance for molecular spectroscopy as the fundamental rotovibrational bands of most light molecules lie in this spectral range, with absorption strength orders of magnitude higher than in the visible or near-infrared 10 .…”
mentioning
confidence: 99%
“…Although first demonstrated in the mid-infrared (MIR) part of the spectrum, dual-comb spectroscopy has been extensively developed in the near-infrared spectral region [5][6][7] , as frequency combs are mature sources in this spectral region. Extending this technique to the MIR range 8 , where the fundamental roto-vibrational transitions of most gas molecules are present, will allow to achieve dual-comb spectroscopy measurements with accuracies and precisions never achieved [9][10][11] .…”
mentioning
confidence: 99%
“…Dual-comb spectroscopy [3][4][5][6] is becoming one of the most attractive spectroscopy techniques based on frequency combs, as all the comb spectrum can be acquired in very short time scales without requiring any moving parts.…”
mentioning
confidence: 99%
“…Kp,03.67.Lx,74.25.nn,85.25.Oj,85.25.Pb Keywords: superconducting, resonator, frequency comb, broadband, RF, microwave Frequency combs in the optical regime have become extremely useful in a wide range of applications including spectroscopy and frequency metrology [1][2][3]. Recently, it was found that a strongly pumped, high-Q optical microcavity made from a nonlinear medium generates sidebands due to a combination of degenerate and nondegenerate four-wave mixing (FWM) [4][5][6] that cascade into a broadband frequency comb of photon energies in the regime of hundreds of THz.…”
mentioning
confidence: 99%